2023
DOI: 10.1371/journal.pone.0286771
|View full text |Cite
|
Sign up to set email alerts
|

Survival, movements, home range size and dispersal of hares after coursing and/or translocation

Abstract: Hare coursing is the pursuit of a hare by dogs for sport. In recent years in Ireland, between 2,900 to 3,700 hares have been caught from the wild (under Government license) and held in captivity for up to 8 weeks. Hares are given a head start and coursed in an enclosed arena by two muzzled greyhounds where the object is not to kill the hare, but judge the dogs on their ability to turn the hare which escapes under a partition through which the dogs cannot follow. Recent licence returns suggest over 99% of hares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…being one such area (Figure 1c). The home range sizes we recorded for the Irish hare population at Dublin Airport were similar to those reported elsewhere in Ireland (Caravaggi et al, 2016;Reid, 2023;Wolfe & Hayden, 1996). Hares do not inherently avoid tarmacked surfaces, however.…”
Section: Discussionsupporting
confidence: 85%
“…being one such area (Figure 1c). The home range sizes we recorded for the Irish hare population at Dublin Airport were similar to those reported elsewhere in Ireland (Caravaggi et al, 2016;Reid, 2023;Wolfe & Hayden, 1996). Hares do not inherently avoid tarmacked surfaces, however.…”
Section: Discussionsupporting
confidence: 85%
“…Among other applications, these tracking approaches can be used to assess the survival of individual study specimens. For example, GPS-enabled tags provide information on the location and activity of tracked specimens that can be used to infer whether and when subjects perish as indicated by the cessation of movements (migratory birds 1 ; hares 2 ; deer 3 ). While applications of GPS-enabled tags have focused on terrestrial specimens, recent studies have demonstrated the utility of popup satellite archival tags for tracking the survival fate of aquatic organisms by monitoring movement accelerations underwater (sharks 4 ; cod 5 ; halibut 6 ).…”
Section: Introductionmentioning
confidence: 99%